Time-series transcriptomics and alternative splicing analysis of embryonic development of the asian honeybee (Apis cerana) - Ding, Xiang; Liu, Zukai; Ou, Linsen; Wang, Zhihui; Xu, Qian; Su, Runlang (Frontiers in Genetics, 2025)
Embryonic development in honeybees is a critical stage that shapes the formation of organs and structures in adult bees. Although there has been substantial progress in transcriptome studies on honeybee embryogenesis, time-series transcriptomic and alternative splicing data in the embryonic development of the Asian honeybee (Apis cerana) remain limited. In this study, we conducted an in-depth analysis of RNA-seq data from public databases to examine the transcriptomic profiles at three key developmental stages of A. cerana embryos (24 h, 48 h, and 72 h), uncovering the dynamic changes in gene expression and alternative splicing across these stages. Results showed that the number of differentially expressed genes and alternative splicing events peaked at 24 and 48 h and then gradually decreased. Time-series transcriptomic analysis further identified key physiological and biochemical processes at these stages, reflecting a progression from foundational metabolism and cellular structure construction in the early stages to cell differentiation and organogenesis in the middle stage, and finally to functional structure refinement and behavioral trait formation in the later stage. Notably, our study highlighted the central role of alternative splicing and gene expression in driving key physiological and morphological changes during embryogenesis. We identified multiple key genes, including DMRT family genes, the Maelstrom (Mael) gene, and highly GO-enriched genes such as Dll, CaMKII, and Cnn. These genes not only play essential roles in structural formation but also support neurodevelopment and the emergence of complex behavioral patterns in adult bees. Gene expression and splicing patterns at different developmental stages provide new insights, revealing the early foundational mechanisms underlying limb development, behavior and memory, sensory organ development, and neural plasticity in honeybees.